Change in MRI-PDFF and Histologic Response in Patients With Nonalcoholic Steatohepatitis: A Systematic Review and Meta-Analysis - Stine, Jonathan G.; Munaganuru, Nagambika; Barnard, Abbey; Wang, Jennifer L.; Kaulback, Kellee; Argo, Curtis K.; Singh, Siddarth; Fowler, Kathryn J.; Sirlin, Claude B.; Loomba, Rohit (Clinical gastroenterology and hepatology, 2021)
Magnetic resonance imaging proton density fat fraction (MRI-PDFF) offers promise as a non-invasive biomarker of treatment response in early-phase nonalcoholic steatohepatitis (NASH) trials. We performed a systematic review to quantify the association between a ≥ 30% reduction in MRI-PDFF and histologic response in NASH. We searched the Cochrane Library, Embase, Medline and trial registries through May 2020 for early-phase clinical trials that incorporated MRI-PDFF and examined histologic response following intervention in adults with NASH. Subjects were classified as MRI-PDFF responders (relative decline in liver fat ≥30%) or non-responders (relative decline in liver fat <30%). MRI-PDFF responders versus non-responders were compared. Primary outcome was histologic response defined as a 2-point improvement in NAFLD Activity Score with at least 1-point improvement in lobular inflammation or ballooning. Secondary outcome was NASH resolution. Proportions and random effects odds ratios (OR) with corresponding 95% confidence intervals (CI) were calculated. Seven studies met inclusion criteria, comprising 346 subjects (median age 51 years; 59% female; 46% with diabetes). MRI-PDFF responders were significantly more likely to have a histologic response (51% vs 14%, P < .001; OR 6.98, 95% CI 2.38-20.43, P < .001) and NASH resolution (41% vs 7%, P < .001; OR 5.45, 95% CI 1.53-19.46, P = .009) compared to non-responders. This meta-analysis demonstrates that a ≥30% relative decline in MRI-PDFF is associated with higher odds of histologic response and NASH resolution. These results support the use of MRI-PDFF in non-invasive monitoring of treatment response in early-phase NASH clinical trials and provide helpful data for sample-size estimation for histology-based assessment.